Experimental and Analytical Study of Different Fiber Reinforced Composites with Damage - Sasikumar, R.; Vinodh, S.; Saravana Kumar, M.; Sabaree, M. (International Journal of Engineering and Technology, 2018)
Composites are the materials which are majorly used in applications of aerospace, defense, transportation, communication, power, electronics, recreations porting and other commercial and consumer products. It is thus becoming more and more important that long term behavioral characteristics of the materials and structures are understood and implications of variety of flaws determined with respect to load conditions. This is to pay particular attention to fiber reinforced composites and its damage. The composites have fibers. Interwoven in orthogonal directions and cracks were introduced in different angles and composites coupons were undergone experimental procedures so that variation of tensile strength and stress strain curves are possible to study their effect on the composites. Different characteristics of damage on failure and remaining life were been clearly viewed by the result of non- linearÂ  finite element models tensile test were carried out using standard conditionsÂ Â